2019
DOI: 10.1167/iovs.18-25823
|View full text |Cite
|
Sign up to set email alerts
|

Following the Status of Visual Cortex Over Time in Patients With Macular Degeneration Reveals Atrophy of Visually Deprived Brain Regions

Abstract: Following the status of visual cortex over time in patients with macular degeneration reveals atrophy of visually deprived brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…However, we can draw on changes to the posterior visual pathway that have been documented in other visual deficits to provide some context ( Prins et al, 2016 ). Previous research has reported significant structural changes in visual processing pathways in the brain both in individuals with congenital blindness ( Ptito et al, 2008 ; Jiang et al, 2009 ; Park et al, 2009 ; Aguirre et al, 2016 ; Bridge and Watkins, 2019 ) and acquired defects ( Boucard et al, 2009 ; Hernowo et al, 2014 ; Brown et al, 2016 ; Prins et al, 2016 ; Hanson et al, 2019 ). Functional changes have been identified in another ophthalmological disorder, i.e., amblyopia, in higher visual areas including V4 and MT+ ( Wong, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we can draw on changes to the posterior visual pathway that have been documented in other visual deficits to provide some context ( Prins et al, 2016 ). Previous research has reported significant structural changes in visual processing pathways in the brain both in individuals with congenital blindness ( Ptito et al, 2008 ; Jiang et al, 2009 ; Park et al, 2009 ; Aguirre et al, 2016 ; Bridge and Watkins, 2019 ) and acquired defects ( Boucard et al, 2009 ; Hernowo et al, 2014 ; Brown et al, 2016 ; Prins et al, 2016 ; Hanson et al, 2019 ). Functional changes have been identified in another ophthalmological disorder, i.e., amblyopia, in higher visual areas including V4 and MT+ ( Wong, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one study detected significant cortical atrophy in patients with AMD at long-term follow-up, with a decline in mean cortical volume across the whole occipital lobe. And what’s significant is this decline could be explained by cortical thinning of the lesion projection zone [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this retinal ganglion cell loss is likely to cause the decreases in visual field map surface areas, and (indirectly) the increases in pRF size, that we observe. For changes in visual field map surface areas, degradation of ascending retinal ganglion cell projections (in macular degeneration) causes a decrease in the gray matter volume in the affected cortical projection zone (Hanson et al 2019 ). Although V2 and V3 do not receive direct ascending projections, V2 is physically linked to V1 and V2 size is correlated with V1 size (Dougherty et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%